Ruminal digestion, gastrointestinal microbial profile, and metabolic pathways after the introduction of silicon-containing ultrafine particles into bull - Elena Sizova; Elena Yausheva; Sergey Miroshnikov; Aina Kamirova; Daniil Shoshin (Veterinary World)
Background and Aim: Nanotechnology offers innovative strategies to enhance livestock productivity and sustainability. Silicon-containing ultrafine particles (UFPs) have shown potential benefits in animal nutrition, yet their effects on gastrointestinal microbial composition and ruminal digestion in cattle remain poorly understood. This study was to evaluate the impact of dietary supplementation with silicon-containing UFPs on ruminal digestibility, bacterial taxonomic structure, and predicted metabolic functions in the gastrointestinal microbiota of cattle.